Phylogenetic analysis of Rhizophora mucronata in Savu Sea Marine National Park, East Nusa Tenggara, Indonesia - IHWAN IHWAN; ESTRI LARAS ARUMINGTYAS; CATUR RETNANINGDYAH; LUCHMAN HAKIM (Society for Indonesian Biodiversity, 2024)
Abstract. Ihwan, Arumningtyas EL, Retnaningdyah C, Hakim L. 2024. Phylogenetic analysis of Rhizophora mucronata in Savu Sea Marine National Park, East Nusa Tenggara, Indonesia. Biodiversitas 25: 4498-4506. Mangroves, a crucial coastal ecosystem, play a crucial role in marine biodiversity and shoreline protection. This study investigates the phylogenetic patterns and haplotype analysis of Rhizophora mucronate, a key mangrove species, in the biodiverse Savu Sea Marine National Park within the Coral Triangle. We collected 30 R. mucronata samples from 15 mangrove populations in the park, including Sumba Island, Sabu Island, Rote Island, and Timor Island. The Maximum Likelihood-based phylogenetic tree reconstruction revealed distinct genetic clusters, segregating populations into two primary clades: Indo-West Pacific (IWP) and Atlantic East Pacific (AEP). Populations from the Sumba, Rote, Semau, Timor, and Sabu Islands primarily aligned with the IWP clade, while some samples exhibited unexpected clustering patterns, indicating potential unique genetic lineages. Notably, populations from Hambapraing and Tesabela showed closer genetic affinity to AEP and the outgroup species, respectively. Our subsequent haplotype analysis further unveiled a complex network of sequence-dependent populations, with notable haplotypes, such as Haplotype 2, showing widespread distribution across Sabu, Sumba, Rote, and Timor, and Haplotype 13 linking populations from Singapore, China, India, USA, Kenya, and Seychelles. These findings not only underscore the complexity of genetics but also highlight the importance of considering distinctive genetic patterns to unravel evolutionary relationships, thereby providing a solid foundation for future research and conservation initiatives.